-W4+3=8

Subtract 3 from both sides of the equation.

-W4=8-3

Subtract 3 from 8.

-W4=5

-W4=5

Multiply both sides of the equation by -4.

-4⋅(-W4)=-4⋅5

Simplify -4⋅(-W4).

Cancel the common factor of 4.

Move the leading negative in -W4 into the numerator.

-4⋅-W4=-4⋅5

Factor 4 out of -4.

4(-1)⋅-W4=-4⋅5

Cancel the common factor.

4⋅-1⋅-W4=-4⋅5

Rewrite the expression.

-1⋅(-W)=-4⋅5

-1⋅(-W)=-4⋅5

Multiply.

Multiply -1 by -1.

1⋅W=-4⋅5

Multiply W by 1.

W=-4⋅5

W=-4⋅5

W=-4⋅5

Multiply -4 by 5.

W=-20

W=-20

Solve for W -W/4+3=8